Strengthening Sustainable Governance to Enhance Government Accountability in the Era of Public Transparency - Meinarni Asnawi; Klara Wonar; Hesty Theresia SALLE Salle; Ryan Arif Turohim (The Indonesian Journal of Accounting Research, 2026)
This study develops an integrated framework to examine how sustainability reporting and governance mediate the relationship between social audit and government accountability in Indonesian local governments. Unlike previous studies that primarily focus on direct relationships, this study investigates the complementary roles of sustainability reporting and governance in strengthening sustainable public governance. A quantitative explanatory design was employed using survey data collected from 197 respondents representing local government institutions in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1. The results indicate that social audit has a positive and significant influence on sustainability reporting, governance, and government accountability. Furthermore, sustainability reporting and governance positively affect accountability and partially mediate the relationship between social audit and accountability. These findings demonstrate that social audit enhances public accountability both directly and indirectly by improving governance quality and strengthening sustainability reporting as an accounting-based accountability mechanism. This study contributes theoretically by integrating Stewardship Theory, Legitimacy Theory, and Stakeholder Theory into a comprehensive framework explaining participatory accountability. Methodologically, it develops and validates an integrated multiple mediation model. Contextually, it provides empirical evidence from Indonesian local governments, highlighting the strategic role of social audit, sustainability reporting, and governance in promoting transparency, sustainable governance, and public sector accountability.